Diagnóstico socioeconômico do programa de aquisição de alimentos no município de Monteiro- PB - Cavalcanti, Natália Thaynã Farias (Universidade Federal de São Carlos, 2016)
The Food Acquisition Program (PAA), sanctioned by the Law number 10.696 of 2nd July, 2003, is one of the specific actions of the Zero Hunger Program, which aims to encourage the family farming, the access to food people in a situation of nutritional and food insecurity and the marketing networks. This study had the general objective to build a diagnosis of PAA in the county of Monteiro, in state of Paraiba in the period of 2011 to 2014, focusing on family farmers, organizations (associations and cooperatives) and institutions which participate in the program, in order to reveal important characteristics of social and economic issues and the consequences of public policy at the municipal level. To achieve the stated goal, the present study was conducted in qualitative and quantitative descriptive, made by an exploratory research, using secondary data SAGI Platform, semi-structured scripts with a recorder and questionnaire. Thus, we held interviews with the program executors (CONAB and county), coordinators of the institutions, nutritionist, presidents of organizations and family farmers. With data and analysis, it was possible to identify positive and negative effects of the program, among the positives are: strengthening organizations and safer production, increase in nominal income, financial independence, increased purchasing power, market insertion and improvement in relations of confidence. The negative were: indebtedness of farmers, frustration, lack of motivation to participation, especially by farmers who developed beneficiation activities, and discontinuity of resources and donations to families in levels of food insecurity. From these findings, It is concluded that the program leveraged organizations and provide an improvement in the socioeconomic conditions of family farmers, however, must occur in the restructuring of the program, given that the limitations directly affect everyone involved.
SOCIOECONOMIC DIAGNOSIS OF FOOD ACQUISITION PROGRAM (PAA) IN THE COUNTY OF MONTEIRO-PB
Keywords: Política pública; Agricultura familiar; Segurança Alimentar; Public Policy; Family farming; Food Safety; CIENCIAS AGRARIAS